A multi-moderator neutron spectrometer for use in BNCT studies of the Tehran research reactor. (August 2021) - Rahmani, Faezeh; Ghal-Eh, Nima; Vega-Carrillo, Hector R.
Abstract: The Tehran Research Reactor is the only appropriate and available neutron source in Iran for clinical boron neutron capture therapy (BNCT). One of the requirements for BNCT is to carefully evaluate and measure the therapeutic neutron beam (epithermal neutrons) as well as the fast and thermal neutron components for successful treatment. In this research, a multi-moderator neutron spectrometer (MMNS) with LiI(Eu) scintillator as neutron counter was proposed for these measurements in the range of 10 −11 eV to 15 MeV. The results confirmed promising precision of the designed MMNS for the epithermal spectrum; however, the angular dependency of the therapeutic beam due to any probable change in the beam-shaping assembly should be considered. Highlights: A multi-moderator neutron spectrometer (MMNS) was designed. MMNS contained LiI(Eu) as a neutron counter. High-density polyethylene and borated water were used as moderators. Modified AFITBUNKI code was used for neutron energy spectrum unfolding . MMNS performed well for epithermal neutron spectroscopy in boron neutron capture therapy.